The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1051/parasite/2016063
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping ofCryptosporidium cuniculusand genotyping ofEnterocytozoon bieneusiin rabbits in two farms in Heilongjiang Province, China

Abstract: Cryptosporidium spp. and Enterocytozoon bieneusi are two prevalent opportunistic pathogens in humans and animals. Currently, few data are available on genetic characterization of both pathogens in rabbits in China. The aim of the present study was to understand prevalence and genetic characterization of Cryptosporidium spp. and E. bieneusi in rabbits. We collected 215 fecal samples from 150 Rex rabbits and 65 New Zealand White rabbits on two different farms in Heilongjiang Province, China. Cryptosporidium spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 63 publications
(84 reference statements)
5
27
1
Order By: Relevance
“…The prevalence of E. bieneusi in the samples in the current study was 2.8% (9/321), which is in accordance with previous studies conducted in China and Spain (Galvan‐Diaz ; Yang et al. ; Zhang et al. ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The prevalence of E. bieneusi in the samples in the current study was 2.8% (9/321), which is in accordance with previous studies conducted in China and Spain (Galvan‐Diaz ; Yang et al. ; Zhang et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of E. bieneusi in the samples in the current study was 2.8% (9/321), which is in accordance with previous studies conducted in China and Spain (Galvan-Diaz 2014;Yang et al 2016;Zhang et al 2016). The nine E. bieneusi isolates in this study belonged to three different genotypes, and phylogenetic analysis revealed that genotype J and BEB8 isolates belonged to group 2, while the Type IV isolates were classed as zoonotic group 1 (Fiuza et al 2016;Li et al 2015).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations